Autoclaved aerated concrete with sulphate content: an environmentally friendly, durable and recyclable building material: Sulfathaltiger Porenbeton: Ein umweltfreundlicher, langlebiger und recyclingfähiger Baustoff. Issue 5 (16th October 2017) - Kreft, Oliver
Abstract: Autoclaved aerated concrete (AAC) contains a small quantity of sulphate. For example, a modern quality class PP2‐0, 35 AAC (λ = 0.09 W/(mK)) from Xella contains about five per cent by mass of sulphate in the form of gypsum or anhydrite. The addition of sulphate reduces shrinkage and enhances compressive strength and durability. AAC thus has an almost unrestricted lifetime. Regarding the environmental acceptability of sulphate, dogmatic discussions have been held for years. What is certain: sulphate is not a hazardous substance. Calcium sulphate (gypsum) has been categorised according to the Directive (EC) No. 1272/2008 (CLP) as not hazardous. Xella's voluntary environmental declarations for AAC confirm not only the excellent ecological balance of this product but also the absence of hazardous substances. For construction and demolition (C&D) waste from AAC, disposal is ensured in Germany with landfill class I ("Non‐hazardous waste, domestic waste"). In order to save disposal costs, Xella offers to take back unmixed cutting waste, which arises in the course of new building or refurbishment, without charge at the Ytong‐factories. Xellas long‐term aim is a closed recycling loop for AAC. A collaborative pilot project between Xella and the Otto Dörner Entsorgung GmbH has shown that from the point of view of process and materials technology, production of high‐quality AAC is even possible under utilization of crushed AAC from demolition.